Hepatectomy in a young patient with advanced hepatocellular carcinoma and poor prognostic imaging features: A case of recurrence-free survival - Huyen Duy Mai Le, MD; Duc Tan Vo, MD, PhD; Hai Trong Do, MD, PhD; Hy Nguyen Gia Le, MD, MSc; Chien Cong Phan, MD; Duy Thanh Nguyen, MD; Quynh Nguyen Diem Le, MD, Msc (Radiology Case Reports)
A 45-year-old male with chronic hepatitis B presented with an advanced hepatocellular carcinoma (HCC) occupying the entire left liver and invading the left portal vein. Despite multiple poor prognostic imaging features, including vascular invasion, corona enhancement, an incomplete capsule, intratumoral necrosis, intratumoral arteries, and irregular tumor borders, the patient elected to undergo a left hepatectomy. Although Barcelona Clinic Liver Cancer (BCLC) staging classified the case as stage C, a resection was successfully performed. Remarkably, 6 years postsurgery, the patient remains recurrence-free. This report highlights a rare, fortunate outcome in a high-risk HCC case and underscores the potential of surgical intervention even in advanced HCC.